2005
DOI: 10.1590/s1806-83242005000200004
|View full text |Cite
|
Sign up to set email alerts
|

Signs and symptoms of temporomandibular disorders in adolescents

Abstract: The aim of this study was to verify the prevalence of signs and symptoms of temporomandibular disorders (TMD) in adolescents and its relationship to gender. The sample comprised 217 subjects, aged 12 to 18. The subjective symptoms and clinical signs of TMD were evaluated, using, respectively, a self-report questionnaire and the Craniomandibular Index, which has 2 subscales; the Dysfunction Index and the Palpation Index. The results of muscle tenderness showed great variability (0.9-32.25%). In relation to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
2
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 22 publications
8
65
2
8
Order By: Relevance
“…However, their sample was young adults around 20 years old. On the other hand, Bonjardim et al 21 also found these signals in adolescents, 26.72% for joint noises and 21.65% for headaches, corroborating the findings of this study which were 25.6% and 20.9% , respectively. Other studies have also found joint noises 21 and headaches 22 as prevalent symptoms, being joint noises the most common one.…”
Section: Discussionsupporting
confidence: 91%
“…However, their sample was young adults around 20 years old. On the other hand, Bonjardim et al 21 also found these signals in adolescents, 26.72% for joint noises and 21.65% for headaches, corroborating the findings of this study which were 25.6% and 20.9% , respectively. Other studies have also found joint noises 21 and headaches 22 as prevalent symptoms, being joint noises the most common one.…”
Section: Discussionsupporting
confidence: 91%
“…A DTM pode acometer indivíduos de várias faixas etárias, incluindo adolescentes; porém, de acordo com a literatura, há um pico de prevalência entre os 35 e 40 anos 15,16 . No presente estudo, foi observada uma média de 34,7 ± 14,5.…”
Section: Discussionunclassified
“…It is important to consider that adolescents experience many developmental challenges as they strive to break away from their parents, become independent, and establish their own identities. 1 However, childhood involves a setting filled with the burden of learning activities, which may contribute to a child's high level of anxiety. In the present study, considering TMD as the dependent variable, children with anxiety were about 18 times more likely to develop TMD than those without anxiety, confirming the role of psychological factors in TMD reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Thus, clinical examination directly focusing on orofacial myofunctional conditions is important in TMD studies. 9 Functional disorders of the stomatognathic system may occur in children 1,10 but are infrequently diagnosed and may consequently result in TMD. In this way, awareness of the early signs and symptoms of TMD-focusing on the assessment of masticatory muscles, the TMJ, and associated structures-may reveal if symptoms are TMD in origin.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
See 1 more Smart Citation